Catalog of New Varieties - Taylor, Lloyd W. H.; Molinari, Nicholas J.; Marinkevich, Zhenya; Kodysz, Michael (KOINON: The International Journal of Classical Numismatic Studies, 2022)
1. Damaskos, Alexander the Great 2. Babylonia, Uncertain Mint 6A, Seleukos (first Babylonian satrapy) 3. Baktria, Ai Khanoum, Coregency of Seleukos 1 and Antiochos 1 4. Drangiana, The Ariaspi 5. Parthia, Andragoras 6. Parthia, Andragoras 7. Parthia, Andragoras 8. Parthia, Andragoras 9. Parthia, Andragoras 10. Parthia, Andragoras 11. Parthia, Andragoras 12. Campania, Teanum Sidicinum 13. Vespasian / Titus, mule, Rome mint 14. Hadrian, Rome mint 15. Hadrian, Eastern mint 16. Antoninus Pius / Faustina I, mule (or hybrid?), Rome mint 17. Marcus Aurelius, Rome mint 18. Marcus Aurelius, Rome mint 19. Marcus Aurelius / Lucius Verus, mule, Rome mint 20. Lucius Verus / Marcus Aurelius, mule, Rome mint 21. Commodus / Lucilla (?), mule or hybrid (?), Rome mint 22. Marcus Aurelius / Commodus, mule, Rome mint 23. Commodus, Rome mint 24. Commodus, Rome mint 25. Commodus, Rome mint 26. Didius Julianus, Rome mint 27. Septimius Severus, Rome mint 28. Septimius Severus, Emesa 29. Geta, Rome 30. Elagabalus, Rome 31. Elagabalus, Rome 32. Elagabalus, Eastern (usually attributed to Antioch) 33. Severus Alexander, Eastern (usually attributed to Antioch)